2021
DOI: 10.1016/j.jbc.2021.100824
|View full text |Cite
|
Sign up to set email alerts
|

The antiviral enzyme viperin inhibits cholesterol biosynthesis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…Such alternations interfere with the replication of several enveloped viruses, including of IAV, that particularly rely on the cellular membranes for virus entry, assembly, and release ( 35 , 36 ). Viperin also targets cholesterol and interferes with its biosynthesis and, consequently, with the replication of multiple enveloped viruses ( 37 ). In case of IAV infection, viperin inhibits the release of budding viral progeny from the host cell plasma membrane by interfering with lipid rafts formation ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such alternations interfere with the replication of several enveloped viruses, including of IAV, that particularly rely on the cellular membranes for virus entry, assembly, and release ( 35 , 36 ). Viperin also targets cholesterol and interferes with its biosynthesis and, consequently, with the replication of multiple enveloped viruses ( 37 ). In case of IAV infection, viperin inhibits the release of budding viral progeny from the host cell plasma membrane by interfering with lipid rafts formation ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic processes and their molecular signaling pathways have the effect on DC development and differentiation [ 17 ]. It is reported that Viperin could inhibit virus infection via reduced cholesterol biosynthesis or improve glucose metabolism [ 29 31 ]. However, in this study, Viperin did not influence cholesterol production or gene expression of important enzymes in the glycolytic pathway including SLC2α, PFKFB3, HK2, PDK1, HIF-1α and TKT (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, many studies corroborate this proposal and demonstrate that human SAND has a role in modulating metabolism, regulating the activity/maturation of the immune cells, and inducing the expression of immune genes ( Figure 1B ). For example, the activity of SAND modulates central carbon metabolism ( Ebrahimi et al, 2020c ), regulates thermogenesis in adipose tissues ( Eom et al, 2019 ), inhibits thiolase activity of the trifunctional enzyme complex (a mitochondrial enzyme complex with three activities: enoyl-CoA hydratase, 3-hydroxyacyl-CoA dehydrogenase, and 3-ketoacyl-CoA thiolase) ( Dumbrepatil et al, 2020 ), and modulates cholesterol metabolism ( Tang et al, 2016 ; Grunkemeyer et al, 2021 ). It is required for optimal T helper two cell response ( Qiu et al, 2009 ) and chondrogenic differentiation via CXCL10 protein secretion ( Steinbusch et al, 2019 ).…”
Section: Main Textmentioning
confidence: 99%